Future Marketing Classroom: Transformasi Metode Pembelajaran Manajemen Pemasaran Melalui Canva - Sabda Aji Kurniawan; Walter Tabelessy; Silfiena Siahainenia; Jacsy Tubalawony; Glen Andre Yusuf T (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
The advancement of digital technology brought significant changes to teaching methods in higher education, particularly through the increasing use of technology-based media such as Learning Management Systems (LMS), instructional videos, and interactive graphic design applications. However, at Pattimura University, the integration of technology into teaching still faced various challenges, especially related to lecturers’ skills in designing engaging and effective digital content. To address this issue, a Community Service Program (PkM) was carried out at the Faculty of Economics and Business, which aimed to enhance lecturers’ competencies in developing instructional videos using the Canva application. The program was implemented through socialization, training, hands-on workshops, and discussion sessions that involved lecturers from the Department of Management, particularly those in the Marketing concentration. The evaluation results showed a significant improvement in lecturers’ ability to utilize Canva for creating interactive slides and instructional videos. This program successfully contributed to improving the quality of teaching, making it more aligned with the needs of students in the digital era. Furthermore, it strengthened the capacity of lecturers in Eastern Indonesia to integrate technology into education, thereby opening opportunities for more creative, collaborative, and relevant teaching practices in line with technological developments.